Innovation of Traditional Salt Pond by Enhancing Evaporation Rate using Coconut Coir Waste - Yani, Setyawati; Yani, Syamsuddin; Artiningsih, Andi; Adawiah, Rifani Rabiatul; Ramadhani, Tarisa (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2024)
National salt production capacity is dominated by smallholder salt production through the crystallization process in traditional salt ponds. One of the salt producing areas in South Sulawesi Province is located in Jeneponto Regency. Salt farmers in Jeneponto Regency produce salt through traditional salt ponds. Jeneponto Regency is also one of the main coconut producing areas. Coconut coir from the people's plantation industry is currently only used as fuel in small and medium home industries or is simply thrown away as waste. Coconut coir has the ability to absorb water. The aim of this research is to innovate the use of coconut coir waste to increase the surface area for water evaporation in traditional laboratory-scale salt ponds. This research was also carried out by conducting analysis on traditional ponds to study the factors that influence the salting process. Next, the salting process was carried out on a laboratory scale by making a replica of the traditional pond salting process which was equipped with the addition of coconut coir to increase the evaporation surface area. The results of the research show that the salting process in traditional salt ponds is greatly influenced by the season. The sun plays a very important role in the evaporation process in traditional salt ponds until salt crystals form in the ponds. Laboratory scale salt pond equipment shows that the use of coconut coir plays a very important role in speeding up the evaporation process and has the potential to increase salt production in traditional salt ponds.